Transcriptional regulation by promoters with enhancer function. Issue 5 (20th October 2018) - Dao, Lan T. M.; Spicuglia, Salvatore
ABSTRACT: Promoters with enhancer activity have been described recently. In this point of view, we will discuss current findings highlighting the commonality of this type of regulatory elements, their genetic and epigenetic characteristics, their potential biological roles in the regulation of gene expression and the underlining molecular mechanisms. Abbreviations: TSS: transcription start site; IFN: interferon; STARR-seq: Self-Transcribing Active Regulatory Region sequencing; MPRA: Massively Parallel Reporter Assay; ChIP: chromatin immunoprecipitation; CRISPR: Clustered Regularly Interspaced Short Palindromic Repeats; lncRNA: long non-coding RNA.